Parental Involvement in English Homework Tasks: Bridging the Gap between School and Home - Nelly Patricia Ávila Daza; Sandra Janneth Garavito (Universidad Nacional de Colombia, 2009)
This paper explores the concept of parental involvement in English homework tasks as a way to include parents in the educational community. This descriptive study was carried out in a female public school with 10 students from third and fourth grades and their parents. In order to obtain the information, different instruments were used: artifacts, interviews, questionnaires and observations. After analyzing the data, it was stated that parental involvement was seen as a means to bridge the gap between the school and home. The findings also showed the possibility of learning from each other and the importance of homework tasks as interactional and learning spaces among parents and children.